Coordinated defects in hepatic long chain fatty acid metabolism and triglyceride accumulation contribute to insulin resistance in non-human primates. - Subhash Kamath; Alberto O Chavez; Amalia Gastaldelli; Francesca Casiraghi; Glenn A Halff; Gregory A Abrahamian; Alberto M Davalli; Raul A Bastarrachea; Anthony G Comuzzie; Rodolfo Guardado-Mendoza; Lilia M Jimenez-Ceja; Vicki Mattern; et al. (PLoS ONE)
Unlabelled Non-alcoholic fatty liver disease (NAFLD) is characterized by accumulation of triglycerides (TG) in hepatocytes, which may also trigger cirrhosis. The mechanisms of NAFLD are not fully understood, but insulin resistance has been proposed as a key determinant. Aims To determine the TG content and long chain fatty acyl CoA composition profile in liver from obese non-diabetic insulin resistant (IR) and lean insulin sensitive (IS) baboons in relation with hepatic and peripheral insulin sensitivity. Methods Twenty baboons with varying grades of adiposity were studied. Hepatic (liver) and peripheral (mainly muscle) insulin sensitivity was measured with a euglycemic clamp and QUICKI. Liver biopsies were performed at baseline for TG content and LCFA profile by mass spectrometry, and histological analysis. Findings were correlated with clinical and biochemical markers of adiposity and insulin resistance. Results Obese IR baboons had elevated liver TG content compared to IS. Furthermore, the concentration of unsaturated (LC-UFA) was greater than saturated (LC-SFA) fatty acyl CoA in the liver. Interestingly, LC-FA UFA and SFA correlated with waist, BMI, insulin, NEFA, TG, QUICKI, but not M/I. Histological findings of NAFLD ranging from focal to diffuse hepatic steatosis were found in obese IR baboons. Conclusion Liver TG content is closely related with both hepatic and peripheral IR, whereas liver LC-UFA and LC-SFA are closely related only with hepatic IR in non-human primates. Mechanisms leading to the accumulation of TG, LC-UFA and an altered UFA: LC-SFA ratio may play an important role in the pathophysiology of fatty liver disease in humans.